Intestinal Failure in Pediatric Vascular Ehlers–Danlos Syndrome: A Case Series and Literature Review - Carolina Percul; Veronica Busoni; Carina Izquierdo; Pablo A. Lobos (Journal of Vascular Diseases, 2025)
Background: Vascular Ehlers–Danlos syndrome (vEDS) is a rare connective tissue disorder characterized by collagen type III deficiency, predisposing to spontaneous arterial, uterine, and intestinal ruptures. While intestinal complications are recognized in vEDS, intestinal failure (IF) secondary to these complications is a rare and potentially life-threatening occurrence. This study aimed to describe the clinical presentation, surgical management, and outcomes of pediatric patients with IF secondary to vEDS and to provide a comprehensive review of the limited existing literature on this challenging clinical scenario. Methods: This study comprises a case series of pediatric patients with IF due to vEDS complications and a comprehensive literature review. Clinical data were collected from medical records, including age at diagnosis, surgical history, complications, nutritional status, and long-term outcomes. A literature review was performed to identify studies reporting gastrointestinal complications, surgical outcomes in pediatric vEDS patients, and cases of intestinal failure. Results: Two pediatric patients with vEDS and IF were included. Both patients experienced intestinal perforations and surgical complications and required long-term parenteral nutrition (PN). One patient required PN for 18 months before achieving enteral autonomy, while the other remains dependent. The literature review included four articles and revealed a high risk of complications, including anastomotic leaks, fistulae, and recurrent perforations, in patients with vEDS undergoing intestinal surgery. Delayed diagnosis of vEDS was common. Conclusions: Intestinal complications in pediatric patients with vEDS can lead to severe short bowel syndrome and long-term PN dependence. Early diagnosis and a multidisciplinary approach are crucial for optimizing patient care and minimizing complications.